Relationship Between Age And Menopausal Status With The Incident Of Epithelial Ovarian Carcinoma At RSUP Dr. M. Djamil Padang - Carmiyana Puja Harsby; Syamel Muhammad; Yenita Yenita (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction : High Grade Serous Ovarian Carcinoma (HGSOC) been the dominant subtype and accounted for the highest mortality rate of epithelial ovarian cancer. Therefore, knowledge of the risk factors for epithelial ovarian cancer was needed for early detection. Age and menopausal status were examples of risk factors. This study aimed to determine the relationship between age and menopausal status with the incidence of epithelial ovarian cancer subtype of HGSOC at M Djamil Central Hospital Padang. Method : This type of research is an observational analytic research design cross-sectional. The form sample is secondary data used in the total sampling method, which comes from 90 patients of ovarian cancer. Research in analysis univariate and bivariate presented in form table frequency. Result : In this study, it was found that epithelial ovarian cancers subtype HGSOC was found mostly in women aged > 50 years (68,9%) and who had experienced menopause (80%). In the analytic test, the p value for age and menopausal status was 0.382 and 0.104. Conclusion: Concluded there is no relationship between age and menopausal status with the incidence of epithelial ovarian cancer subtype HGSOC at M Djamil Central Hospital Padang